Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.2007.0906-7590.05251.x
|View full text |Cite
|
Sign up to set email alerts
|

Demography of alpine red squirrel populations in relation to fluctuations in seed crop size

Abstract: Vertebrate population dynamics, social organisation and space use often are closely associated with the distribution of critical resources, such as food. Tree squirrels are ideal models to study these relationships, since both key demographic parameters (reproduction, survival and dispersal) and spatio-temporal variation in food supplies (measured as seed-crop size) can be reliably estimated. In this paper we test the following two predictions underlying the association between annual food abundance and demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(116 citation statements)
references
References 80 publications
(194 reference statements)
1
114
1
Order By: Relevance
“…Densities of red squirrels in montane spruce-fir forests are low and comparable with other types of "low quality" conifer habitats in Europe (Gurnell 1987;Lurz et al 1995;Wauters et al 2008). However, space-use patterns in lowdensity populations are rarely investigated (Lurz et al 2000;Bryce et al 2002;Dahle and Swenson 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Densities of red squirrels in montane spruce-fir forests are low and comparable with other types of "low quality" conifer habitats in Europe (Gurnell 1987;Lurz et al 1995;Wauters et al 2008). However, space-use patterns in lowdensity populations are rarely investigated (Lurz et al 2000;Bryce et al 2002;Dahle and Swenson 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Two sites in the Cogne (COG) and Rhemes (RHE) Valleys of the Gran Paradiso National Park (western Alps), and four sites in the Valtellina Valley, Central Alps: Cedrasco (CED), OGA, Valfurva (VAL), and Bormio (BOR). Details of the study populations, squirrel density, landscape, tree species composition and specific location and distances between study sites have been reported previously (e.g., Trizio et al 2005;Wauters et al 2008). The social system of this species is based on, predominantly intra-sexual, hierarchical relationships formed through agonistic encounters between both resident and immigrant individuals, and intrasexual territoriality among adult, reproducing females Dhondt 1989, 1992;Wauters et al 1990).…”
Section: Study Areas and Populationsmentioning
confidence: 99%
“…Hence, not all juveniles were marked before reaching age at which dispersal starts (4-5 months old, Dhondt 1993, 1995) and might have been classified incorrectly as immigrants. To estimate whether and to what extend classification of individuals as locally born offspring, or as immigrants, using CMR (e.g., Wauters et al 2004Wauters et al , 2008 was correct, we compared their assignment by CMR with genetic offspring assignment using CERVUS.…”
Section: Introductionmentioning
confidence: 99%
“…its diet depends on the environment where squirrel is found and also changes throughout the year depending on food availability (Krauze-gryz, gryz 2015). however, red squirrel more highly prefers seeds of coniferous and broadleaved trees, whilst squirrel population density fluctuates depending on the seed availability (lurz et al 1995;Wauters et al 2008). red squirrel population densities are higher in places where food availability is steady throughout the year (Wauters et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…however, red squirrel more highly prefers seeds of coniferous and broadleaved trees, whilst squirrel population density fluctuates depending on the seed availability (lurz et al 1995;Wauters et al 2008). red squirrel population densities are higher in places where food availability is steady throughout the year (Wauters et al 2008). During the periods when main food supply of tree seeds is low, red squirrels try to locate the more productive tree groups within their forest, increase their home ranges or migrate (lurz et al 2000;Wauters et al 2005).…”
Section: Introductionmentioning
confidence: 99%